Pencegahan dan Pemberantasan Stunting Bersama Kader Pkk di Desa Wonosari Kecamatan Bengkalis - Sumarto Sumarto; Bercahaya Siregar; Muslika Sari; Parlin Edward; Yehezkiel Andersen; Devina Adelia; Wegadanata Pakpahan; Sakinah Sakinah; Natasya Margaretha; Tri Oktav Cahya Ningrum (jurnal ABDIMAS Indonesia, 2023)
Stunting is a growth and development disorder in children caused by poor nutrition and frequent and insufficient psychosocial stimulation infections. Stunting usually occurs due to several factors such as environmental factors, genetic factors, socioeconomic conditions, infectious diseases and exclusive breastfeeding. In DISKOMINFOTIK Bengkalis Regency, it is said that the prevalence of stunting in Bengkalis Regency in 2021 will reach 21.9 percent and drop to 8.4 percent in 2022. This is what caused us as KKN Bangun Kampung students at Riau University to realize the socialization of stunting in Wonosari Village as our flagship program. From these conditions, we as KKN Bangun Kampung Wonosari Village Students together with the head of the PKK and Posyandu cadres make every effort to provide knowledge about the understanding, symptoms and ways to prevent stunting to PKK mothers and members of the Wonosari Village posyandu cadre.